The Effect of Economic Value Added, Market Value Added, Earnings Per Share and Firm Size on the Return of Islamic Stocks in Manufacturing Companies Listed in ISSI - Irawan, Dedi; Idris, Muhammad; Fauzi, Fauzi (Opción, 2019)
This study is intended to determine the effect of economic value added, mar- ket value added, earnings per share and firm size on Islamic stock returns in manufacturing companies listed in the Indonesian Sharia Stock Index 2015-2017. This research was analyzed using error correction models or commonly used as ECM abbreviations. The sample in this study was ob- tained as many as 30 companies that joined the Indonesian Sharia Stock Index. The results show that the variables EVA, MVA, EPS and firm size have a significant effect on stock returns both in the short and long term as indicated by the probability value of F statistic 0.041232 in the long run and short term of 0.00000 where the results are more a small number of α = 5% and a F value of statistics greater than F table. Based on data analysis that has been done it can be seen that the EVA variables both long term and short term have no effect on stock returns.